2001
DOI: 10.1034/j.1600-0706.2001.950104.x
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation processes and persistence in remnant water vole populations

Abstract: We examined the spatial distribution of water vole populations in four consecutive years and investigated whether the regional population processes of extinction, recolonisation and migration influence distribution and persistence. We examined how such regional processes are influenced by spatial variation in habitat quality. In addition, we assessed the relevance of metapopulation concepts for understanding the dynamics of species that deviate from classical metapopulation assumptions and developing conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 29 publications
(32 reference statements)
1
60
0
Order By: Relevance
“…Not considering stage structure produced biased estimates of the scale of dispersal (log(2)/a: juvenile ¼ 12.40 km vs. total population ¼ 5.52 km). That juveniles should be a more informative determinant of colonization is biologically consistent with observations in water voles that most movement happens early in life ( juvenile natal dispersal), as is the case for most small-mammal species (Telfer et al 2001, Le Galliard et al 2011. It is also sensible that adult population size should determine the fate of patches in terms of their extinction risk for two reasons.…”
Section: Discussionmentioning
confidence: 72%
“…Not considering stage structure produced biased estimates of the scale of dispersal (log(2)/a: juvenile ¼ 12.40 km vs. total population ¼ 5.52 km). That juveniles should be a more informative determinant of colonization is biologically consistent with observations in water voles that most movement happens early in life ( juvenile natal dispersal), as is the case for most small-mammal species (Telfer et al 2001, Le Galliard et al 2011. It is also sensible that adult population size should determine the fate of patches in terms of their extinction risk for two reasons.…”
Section: Discussionmentioning
confidence: 72%
“…Small vole populations in the tawny owl study area in the UK (Kielder Forest) are a stable food resource that show spatial synchrony in their numbers across all suitable habitat patches (MacKinnon et al 2001). Water voles are, presumably, a less predictable food supply than small voles are, because water vole populations are highly patchily distributed in the landscape, are frequently absent from suitable habitat and are characterised by frequent population turnovers (Aars et al 2001;Telfer et al 2001). Studies of food supply, diet and sex allocation in tawny owls in additional populations may, therefore, contribute to our general understanding of sex allocation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…By suppressing population booms following high summer rainfall, feral mink may be removing a major impetus for voles to disperse and recolonise vacant islands to disrupt the natural metapopulation dynamic. Recently Telfer et al (2001) also suggested that the metapopulation dynamics of water voles in a river system in England were being disrupted by American mink via elevated extinction rates that would also reduce colonisation events. Such a phenomenon may also occur with our voles on very small islands to contribute to an erosion of metapopulation processes, although the ability of mink to directly cause local extirpation is not clear as we found that mink removal alone did not explain extinction events.…”
Section: Discussionmentioning
confidence: 99%